The good, the bad, and the unknown nature of decreased GD3 synthase expression - Puljko, Borna; Grbavac, Josip; Potočki, Vinka; Ilic, Katarina; Viljetić, Barbara; Kalanj-Bognar, Svjetlana; Heffer, Marija; Debeljak, Željko; Blažetić, Senka; Mlinac-Jerkovic, Kristina (Frontiers in molecular neuroscience, 2024)
This paper explores the physiological consequences of decreased expression of GD3 synthase (GD3S), a biosynthetic enzyme that catalyzes the synthesis of b-series gangliosides. GD3S is a key factor in tumorigenesis, with overexpression enhancing tumor growth, proliferation, and metastasis in various cancers. Hence, inhibiting GD3S activity has potential therapeutic effects due to its role in malignancy-associated pathways across different cancer types. GD3S has also been investigated as a promising therapeutic target in treatment of various neurodegenerative disorders. Drugs targeting GD3 and GD3S have been extensively explored and underwent clinical trials, however decreased GD3S expression in mouse models, human subjects, and in vitro studies has demonstrated serious adverse effects. We highlight these negative consequences and show original mass spectrometry imaging (MSI) data indicating that inactivated GD3S can generally negatively affect energy metabolism, regulatory pathways, and mitigation of oxidative stress. The disturbance in several physiological systems induced by GD3S inhibition underscores the vital role of this enzyme in maintaining cellular homeostasis and should be taken into account when GD3S is considered as a therapeutic target.